(3EfSGf GdYjhf aj SjQI GdCejf GdeCehf Udi Gddg Ydjg hSdes - (3GdMdHj, CHh GdaQL, GHf HQgGf GdOjf, fhQ GdOjf, Ydj Hf EHQGgje Hf CMeO, J (B1044 (3g`s
(3ChdgG (B:s
(3MeOG def fVQ hLhg Cgd GdMOjK hHYO ajbhd Ydj Hf HQgGf GdOjf GdMdHj GdTGaYj Cf SjQI GdeUWai Ydjg CaVd GdUdGI hGdSdGe ef Cge eG GgJe Hg GdYdeGA GdCYdGes
(3BNQgG (B:s
(3eYGhjI aj NdGaJg hQKg HGdCNhI eY hLhO ChdGOg Ke QCjJ GdMGaX GHf MLQ aj GdEUGHI PcQ Pdc hfXQ ajgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 251s
(3eYLe GdeDdajf(B: 2 / 386s
(3cTa GdXfhf(B: 1 / 180s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJGQjNs